Immunotherapy with Listeria reduces metastatic breast cancer in young and old mice through different mechanisms - Jahangir, Arthee (Oncoimmunology, 2017)
Cancer immunotherapy is one of the most promising and benign therapies against metastatic cancer. However, most cancer patients are old and elderly react less efficient to cancer vaccines than young adults, due to T cell unresponsiveness. Here we present data of cancer vaccination in young and old mice with metastatic breast cancer (4T1 model). We tested adaptive and innate immune responses to foreign antigens (Listeria-derived) and self-antigens (tumor-associated antigens (TAA)) and their contribution to elimination of metastases at young and old age. Three different protocols were tested with Listeria: a semi- and exclusive-therapeutic protocol both one-week apart, and an exclusive therapeutic protocol frequently administered. Adaptive and innate immune responses were measured by ELISPOT in correlation with efficacy in the 4T1 model. We found that Listeria induced immunogenic tumor cell death, resulting in CD8 T cell responses to multiple TAA expressed by the 4T1 tumors. Only exclusive therapeutic frequent immunizations were able to overcome immune suppression and to activate TAA- and Listeria-specific CD8 T cells, in correlation with a strong reduction in metastases at both ages. However, MHC class Ia antibodies showed inhibition of CD8 T cell responses to TAA at young but not at old age, and CD8 T cell depletions in vivo demonstrated that the T cells contributed to reduction in metastases at young age only. These results indicate that CD8 T cells activated by Listeria has an antitumor effect at young but not at old age, and that metastases at old age have been eliminated through different mechanism(s).